Primary Central Nervous System Lymphoma Mimicking Longitudinally Extensive Transverse Myelitis. (April 2021) - Natteru, Prashant Anegondi; Shekhar, Shashank; Nair, Lakshmi Ramachandran; Uschmann, Hartmut
Primary central nervous system lymphoma (PCNSL) is an uncommon variant of extra-nodal non-Hodgkin's lymphoma. Three regions can be involved in PCNSL: the brain, the spine, or the vitreus and retina. Spinal PCNSL is rare. It can mimic neoplasm, infection, and inflammation. Diagnostic confirmation is by tissue biopsy, and even then, tissue corroboration may be altered by an inflammatory overlay. We report a 59-year-old woman who we saw after she had 4 weeks of ascending tetraparesis plus bowel and bladder incontinence. Upon presentation, the patient was ventilator-dependent and locked-in. She reported normal sensation through eye-blinking. Magnetic resonance imaging (MRI) brain revealed signal intensity in the bilateral corona radiata and restricted diffusion in the right thalamus, whereas, MRI cervical, and thoracic spine showed T2 prolongation in the anterior medulla and upper cervical cord, with enhancement to C2-C3, and long segment hyperintensity from T1-T9 levels, respectively, suggestive of neuromyelitis optica spectrum disorder. Cerebrospinal fluid cytomorphology and flow cytometry were inconclusive for lymphoma/leukemia, but oligoclonal bands were present. Serum aquaporin-4 (AQP-4) antibodies were negative. MR spectroscopy demonstrated NAA reduction, mild lipid lactate peak, and relative reduction of choline on the side of the lesion, favoring demyelination. She received 5-days of intravenous methylprednisolone, followed by 7 sessions of plasma exchange without clinical improvement. Stereotactic biopsy of the right thalamic lesion revealed diffuse large B-cell lymphoma. PCNSL can mimic a demyelinating process early on, as steroid treatment could disrupt B-cell lymphoma cells, thus masking the correct diagnosis.